The Penguin History of Early India from the Origins to AD 1300 in Urdu - Romila Thapar (My University, 2017)
The text gives its readers an exhaustive idea about the history of India, from the time of its formation, through its gradual coalition, to its structure in AD 1300. The account is not a chronological narration of the events that took place to form India, but the narration of many stories of the different parts of India which gradually came together to form one great country.
Keywords: Urdu